Beyond Commodity Prices: Industrial Metals and Long-Run Economic Growth in Indonesia - Hariono, Hariono; Sapriyadi, Sapriyadi; Anggraini, Yuyun (Universitas Pasundan, 2025)
This study investigates the long-run and nonlinear relationship between industrial metal prices and economic growth in Indonesia by interpreting aluminum and copper prices as structural proxies for global industrial metabolism. Moving beyond conventional commodity-price analysis, the study employs a time-series econometric framework integrating unit root tests, ARDL bounds cointegration, error correction modeling, and threshold analysis. Using long-horizon annual data, the findings reveal a stable long-run equilibrium relationship between Indonesia’s real GDP and industrial metal proxies, indicating that national economic growth is structurally embedded in material-intensive global production dynamics. The long-run estimates show that aluminum prices exert a positive effect on economic growth, reflecting their role in supporting broad-based industrial throughput and manufacturing expansion. In contrast, copper prices display a negative long-run effect, suggesting that rising material complexity and infrastructural intensity may constrain growth. The nonlinear results further identify a critical copper-price threshold beyond which its impact on growth becomes strongly negative, signaling a transition from productive expansion to systemic industrial stress. These findings underscore the importance of accounting for structural and nonlinear dynamics when assessing growth trajectories in resource-rich developing economies.